Association between Individual, Physical, and Organisational Risk Factors and Low Back Symptoms Among Karawang Industrial-Indonesia Manufacturing Workers - Noviaji Joko Priono; Baiduri Widanarko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Individual and physical risk factors are reported to increase the risk of low back symptoms (LBS) among workers. This study aimed to identify the association between individual, organisational, and physical risk factors and the occurrence of subjective complaints in LBS among Karawang Industrial-Indonesia manufacturing workers.  This preliminary study was cross-sectional. Data in October 2018 were gathered via an online survey using a self-administered questionnaire in 204 workers.  The prevalence of LBS was 75.9%. Some risk factors were associated with LBS such as males (OR 4.82, 95% CI 2.26–10.26), overweight (OR 3.54, 95% CI 1.46–8.58), smokers (OR 2.07, 95% CI 1.07–3.99), and regular exercise during the last 30 days (OR 0.19, 95% CI 0.08–0.40), compared with females, normal weight, non-smokers, and never engaged in regular exercise, respectively. Lifting heavy load (>20 kg) also showed a significant association with LBS (OR 3.97, 95% CI 1.59–9.94).  Interventions aimed at reducing LBS limit the lifting activity, particularly with objects >30 kg, with a focus on smokers, and overweight workers also never engaged in regular exercise. Meanwhile workers also must improve exercise habit.